Patient Safety Culture, Transformational Leadership, and Employee Safety Behavior: Evidence from A Primary Healthcare Facility in Indonesia - Sessika Yunisa; Nurdin Nurdin; Titik Respati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Patient safety in primary healthcare depends not only on formal safety procedures but also on the organizational environment and leadership that shape employees’ safety-related behavior. This study examined the relationship of patient safety culture and transformational leadership with employee safety behavior at UPTD Puskesmas Cipadung, Bandung, Indonesia. A quantitative cross-sectional study was conducted in 2026 using total population sampling involving all 39 employees of the health center. Data were collected using structured questionnaires measuring patient safety culture, transformational leadership, and employee safety behavior on a four-point Likert scale. Data were analyzed using descriptive statistics, Cronbach’s alpha, Spearman correlation, and multiple linear regression. The findings showed that patient safety culture was perceived as very high (mean = 3.83), transformational leadership was very high (mean = 3.84), and employee safety behavior was very high (mean = 3.86). Incident reporting had the highest mean among the patient safety culture dimensions (3.88), while intellectual stimulation was the highest transformational leadership dimension (3.87). Employee safety behavior showed similarly high levels of safety compliance (3.86) and safety participation (3.85). Multiple linear regression showed that patient safety culture had a positive and significant effect on employee safety behavior (β = 0.620; p < 0.001), while transformational leadership also had a positive and significant effect (β = 0.516; p = 0.001). The regression model was statistically significant (F = 64.828; p < 0.001) and explained 78.3% of the variance in employee safety behavior (R² = 0.783). Patient safety culture demonstrated the stronger relative contribution, although transformational leadership also made a significant independent contribution. These findings indicate that employee safety behavior in primary healthcare is associated with both a supportive patient safety culture and transformational leadership. Strengthening safety culture through open communication, incident reporting, teamwork, organizational learning, and employee participation, together with leadership that encourages motivation and problem solving, may support the sustainability of safe practices in primary healthcare.